The Influence of the Role Playing method in storytelling on the confidence of grade V students in Indonesian subjects - Sholihah, Aghnia Ilman (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
Confidence is an important aspect of a student's self-development, however, many students still show a low level of confidence when speaking in front of the class. This study aims to determine the influence of the role playing method in storytelling on the confidence of grade V students in Indonesian subjects. In storytelling, confidence plays a crucial role because students are required to speak fluently, express emotions, and convey the message of the story in an attractive way in front of the audience. This study uses a pre-experimental method with a one group pre-test post-test design. The population of this study is all grade V students of SDN Gelam 2 Serang City. The type of sample used was saturated sampling with the number of samples used, namely 30 students. Data was collected through observation sheets and student confidence questionnaires before and after the application of the role playing method. The results of the study show that the role playing method in storytelling significantly increases students' confidence. This is evidenced by a comparison of the analysis of pre-test data of students who obtained an average score of 53.00 in the sufficient category, and the analysis of post-test data of students who obtained an average score of 65.00 in the high category. The results of the inferential analysis in the form of a hypothesis test with a significance level of 0.000 < 0.05 and the Normalized Gain Score test which obtained a value of 0.4418, both analyses showed that the role playing method had an influence on student confidence. Through this method, students are more active, expressive, and able to express stories better. This research contributes to the implementation of effective learning strategies in improving students' confident character, especially in storytelling learning in elementary schools
Keywords: confidence; learning methods; role playing; storytelling